Produção e qualidade do biogás gerado com os dejetos de diferentes espécies animais - Zanato, Joseli Alves Ferreira [UNESP] (2014)
This trial aimed to evaluate the best dilution for pig, laying hens, sheep, goats, beef cattle and dairy cattle manure to supply digesters, as well as the influence of the solids separation in those same wastes on the production and quality of biogas, on the potential of biogas production and solids reduction. For the dilution test the wastes were diluted with water in the proportions 1:4, 1:5, 1:6, 1:7 and 1:8 (kg of manure per kg of water) and adopted the physical process of screening (sieve with square meshes of 0.75, 1.00 and 1.50 mm) for separation of solids. When tested for anaerobic digestion (batch and semi-continuous digesters) separation of solids was made with 1 mm mesh sieve and substrates of about 4% total solids. Dilution test: although the results varied among the types of manure, generally a 1.50 mm mesh sieve allowed greater flow of solids. But in relation to the dilution used each type of waste had a different response. Testing of anaerobic digestion (batch digesters): although for each manure the process of anaerobic digestion has had a different result, generally solids separation provided better biogas quality, but it was not efficient to increase the potential of biogas production and reduce solids of substrate. Testing of anaerobic digestion (semi-continuous digesters): for the wastes (laying hens and dairy cattle) used the solids separation provided better quality of biogas, lower biogas production, greater reduction of solids and in regards to the potential of biogas production the results were almost always positive. It was concluded that for dilution and sieves test results did not allow a general conclusion for all waste reviews, because each one had individual characteristics and, the separation of solids is an efficient method to enhance the quality of the biogas produced, but in relation to the potential of biogas production and solids reduction of the substrate ...